Penerapan Riset Aksi Partisipatif dalam Meningkatkan Kualitas Pembelajaran di SD Negeri 060915 Kecamatan Medan Sunggal - Mujhirul Iman; Wahyu Syahputra; Lingghom Miranda Hanum Pakpahan; Evi Sundari; Dedi Rusdi Pohan; Muhammad Hadi Furqon; Ananda Zahwa (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to improve the quality of learning at SD Negeri 060915, Medan Sunggal District, through the implementation of a participatory learning approach using Participatory Action Research (PAR). The background of the study is based on the low level of student engagement in classroom activities and the teacher’s reliance on traditional lecture methods, which hinder active student participation. This classroom action research was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation, interviews, documentation, and formative assessments. The results showed that the participatory learning approach had a positive impact on increasing student engagement, collaboration in group work, and academic performance, as indicated by an increase in the average student score from 66.4 in the first cycle to 77.2 in the second cycle. Teachers also improved their role as facilitators, and the classroom environment became more interactive and student-centered. The study concludes that the participatory approach is effective in creating an active, collaborative, and meaningful learning environment in elementary education.